2019
DOI: 10.1002/jclp.22740
|View full text |Cite
|
Sign up to set email alerts
|

Struggling to be a person: Lived experience of avoidant personality disorder

Abstract: Objective: To better understand the subjective lived experience of persons diagnosed with avoidant personality disorder (AVPD).Methods: Persons with an AVPD (N = 15) were interviewed twice with semistructured qualitative interviews and analyzed through interpretative-phenomenological analysis.Persons with first-hand experience of AVPD were included in the research process.Results: The superordinate theme, "struggling to be a person," encompassed two main themes. The first, "fear and longing," incorporated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(73 citation statements)
references
References 57 publications
2
70
0
1
Order By: Relevance
“…In one of these studies, psychosocial dysfunction measured by WSAS was associated with AVPD beyond other psychopathology (both symptom disorders and other PDs) (Eikenaes et al, 2013). In another recently published Norwegian qualitative study, help-seeking patients with AVPD were interviewed about their everyday life experiences (Sørensen, Råbu, Wilberg, & Berthelsen, 2019). The authors concluded the followings: "Overall, the findings revealed how the participants' efforts at sense-making of their own experiences sometimes resulted in the questioning of their identity and sense of agency -leaving them bereft of options for resolving their rational problems" (p. 675).…”
Section: The Four Domains As Predictor For Wsasmentioning
confidence: 99%
“…In one of these studies, psychosocial dysfunction measured by WSAS was associated with AVPD beyond other psychopathology (both symptom disorders and other PDs) (Eikenaes et al, 2013). In another recently published Norwegian qualitative study, help-seeking patients with AVPD were interviewed about their everyday life experiences (Sørensen, Råbu, Wilberg, & Berthelsen, 2019). The authors concluded the followings: "Overall, the findings revealed how the participants' efforts at sense-making of their own experiences sometimes resulted in the questioning of their identity and sense of agency -leaving them bereft of options for resolving their rational problems" (p. 675).…”
Section: The Four Domains As Predictor For Wsasmentioning
confidence: 99%
“…Persons diagnosed with AVPD experience considerable ongoing fear and insecurity, and work hard to endure these, while longing for connection, both to themselves and others (Sørensen et al, 2019). The participants in this study expressed how they search for answers regarding how they can become able to overcome their fears and insecurities and accomplish their goals.…”
Section: Discussionmentioning
confidence: 95%
“…Previously, we reported from our qualitative research project on the subjective lived experiences of AVPD as it relates to everyday life challenges and strategies (Sørensen et al, 2019). Their everyday lives came across as characterized by an ongoing struggle with sense making, sense of agency, and identity, as the participants both feared and longed for connection with others and described searching for a sense of self.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we reported findings from our qualitative research on the subjective lived experience of AVPD as it relates to everyday life challenges and strategies (Sørensen, Råbu, Wilberg, & Berthelsen, 2019). The findings highlighted an ongoing struggle with sense‐making, the sense of agency and identity, as participants both feared and longed for connection with others and described searching for a sense of self (Sørensen et al, 2019). Another topic addressed in the research project was how persons diagnosed with AVPD make sense of the origin, causes, or development of current everyday concerns.…”
Section: Introductionmentioning
confidence: 99%